2006
DOI: 10.1111/j.1365-2966.2006.11098.x
|View full text |Cite
|
Sign up to set email alerts
|

Atmosphere models of magnetized neutron stars: QED effects, radiation spectra and polarization signals

Abstract: Observations of surface emission from isolated neutron stars (NSs) provide unique challenges to theoretical modelling of radiative transfer in magnetized NS atmospheres. Recent work has demonstrated the critical role of vacuum polarization effects in determining NS spectra and polarization signals, in particular the conversion of photon modes (due to the ‘vacuum resonance’ between plasma and vacuum polarization) propagating in the density gradient of the NS atmosphere. Previous NS atmosphere models incorporate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 74 publications
(182 reference statements)
5
123
0
Order By: Relevance
“…Thermal radiation has been detected from radio pulsars and radio-quiet neutron stars (NSs; see Kaspi et al 2006;Haberl 2007;van Kerkwijk & Kaplan 2007;Zavlin 2007 for reviews) and from soft gamma-ray repeaters and anomalous X-ray pulsars, which form the magnetar class of NSs endowed with superstrong (B k 10 14 G) magnetic fields (see Woods & Thompson 2006 for a review). Radiation from the surface of these NSs can provide invaluable information on the physical properties and evolution of the NSs.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal radiation has been detected from radio pulsars and radio-quiet neutron stars (NSs; see Kaspi et al 2006;Haberl 2007;van Kerkwijk & Kaplan 2007;Zavlin 2007 for reviews) and from soft gamma-ray repeaters and anomalous X-ray pulsars, which form the magnetar class of NSs endowed with superstrong (B k 10 14 G) magnetic fields (see Woods & Thompson 2006 for a review). Radiation from the surface of these NSs can provide invaluable information on the physical properties and evolution of the NSs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the distance to SGR 0418 is rather uncertain. If located in the Perseus arm (which is in its direction), then the distance would be about 2 kpc (van der Horst et al 2010). However, there is no independent observational link to such an association.…”
Section: Spectral Models For Sgr 0418+5729mentioning
confidence: 99%
“…While the magnetar model has been very successful in explaining some general features of the triggering mechanism of bursts and flares, the discovery in 2010 of an outburst from SGR 0418+5729 (SGR 0418 hereafter, van der Horst et al 2010;Esposito et al 2010), a NS with dipolar magnetic field B dip = (6 ± 2) ×10 12 G (Rea et al 2010, lower than those of most magnetars, clearly showed that the overall picture was not complete. Following this discovery, two more sources showing magnetar-like activity, but with "non-magnetar"-like B fields have then been discovered (Rea et al 2012;Scholz et al 2012;Rea et al 2014;Zhou et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…• [377] (see also [378]). These calculations have thus fully confirmed the early analysis by Gnedin and Sunyaev [11].…”
Section: Spectra Of Magnetic Photospheresmentioning
confidence: 99%